Pathogenic Bacterial Detection Using Vertical-Capacitance Sensor Array Immobilized with the Antimicrobial Peptide Melittin - Sun-Mi Lee; Jun-Ho Song; Kyo-Seok Lee; Kyung-Hwa Yoo (Sensors)
The rapid and reliable detection of pathogenic bacteria remains a significant challenge in clinical microbiology. Consequently, the demand for simple and rapid techniques, such as antimicrobial peptide (AMP)-based sensors, has recently increased as an alternative to traditional methods. Melittin, a broad-spectrum AMP, rapidly associates with the cell membranes of various gram-positive and gram-negative bacteria. It also inhibits bacterial biofilm formation in blood culture media. In our study, bacterial growth was measured using electrical vertical-capacitance sensors with interdigitated electrodes functionalized with melittin, a widely studied AMP. The melittin-immobilized vertical-capacitance sensors demonstrated real-time detection of both standard and clinically isolated bacteria in media. Furthermore, these sensors successfully detected clinically isolated bacteria in blood culture media while inhibiting bacterial biofilm formation. Melittin-immobilized vertical-capacitance sensors provide a rapid and sensitive pathogen detection platform, with significant potential for improving patient care.